The impact and reflection of grid-based urban medical consortium construction on community coronary heart disease patients—Taking the Cardiology Department of an integrated Traditional Chinese Medicine and Western Medicine hospital as an example (网格化城市医联体建设对社区冠心病患者的影响与思考) - ZHENG Tairong (郑太蓉); ZENG Min (曾敏); YU Linlin (余琳琳); SONG Yingchanxi (莹婵茜); SU Shuili (苏水利) (中西医结合护理)
Objective To explore the impact on community coronary heart disease patients under the construction of grid-based urban medical consortia. Methods Based on the grid-based urban medical consortium led by Chengdu Integrated Traditional Chinese and Western Medicine Hospital, a cross-sectional survey was conducted to compare the Case-mix Index(CMI) and Relative Weight(RW) values, total hospitalization costs, length of stay, and number of consultations of all coronary heart disease referral patients who transferred from the community to Chengdu Integrated Traditional Chinese and Western Medicine Hospital from January to September 2022 and January to September 2023 through percentage calculation and non-parametric tests with independent samples, Analyze the current situation and existing problems of the construction between the Cardiology Department of Chengdu Integrated Traditional Chinese and Western Medicine Hospital and the linked community. Results After building a grid-based urban medical consortium, the number of patients with coronary heart disease who were transferred to the community increased by 17. 95% year-on-year, the CMI value increased by 0. 73%, the total hospitalization cost decreased by 13. 97%, the length of hospital stay decreased by 9. 28%, and the number of consultations decreased by 16. 67%; The total hospitalization cost showed a significant difference between January September 2022 and January September 2023, with a significant difference (P＜0. 01). Conclusion The construction of a grid-based urban medical consortium can reduce hospitalization costs for patients with coronary heart disease, alleviate their economic burden, and alleviate the pressure on medical insurance funds. (目的 探讨网格化城市医联体建设对社区冠心病患者的影响。方法 以成都市中西医结合医院牵头构建的网格化城市医联体为基础, 采用横断面调查方法, 通过计算百分比和独立样本的非参数检验, 对比2022年1月—9月和2023年1月—9月从社区转至成都市中西医结合医院的所有冠心病转诊患者的病例组合指数(CMI)值、相对权重(RW)值、住院总费用、住院日、会诊次数, 分析成都中西医结合医院心内科与联动社区之间的建设现状及存在的问题。结果 在构建网格化城市医联体后, 社区冠心病上转患者的数量同比提升17. 95%, CMI值升高0. 73%, 住院总费用下降13. 97%, 住院天数减少9. 28%, 会诊次数降低16. 67%; 住院总费用2022年1月—9月和2023年1月—9月比较, 差异有统计学意义(P＜0. 01)。结论 网格化城市医联体建设可以为冠心病患者降低患者的住院费用, 减轻患者的经济负担, 缓解医保基金压力。)